Building Condition Assessment (BCA) at Tun Syed Nasir Residential College, UTHM. - Mohd, Nurul Syafiqqah; Deraman, Rafikullah (Recent Trends in Civil Engineering and Built Environment, 2023)
Building Condition Assessment (BCA) is a popular method for determining the physical state of an existing structure. BCA entails identifying and evaluating defects and deterioration in building elements and services, as well as determining the maintenance work needed to keep the building in good condition. Tun Syed Nasir Residential College, which has been occupied for nearly 28 years, is more prone to flaws due to increased wear and tear and a lack of proactive maintenance. Thus, this study was performing a building inspection through BCA on the Tun Syed Nasir Residential College as a case study to evaluate the building’s condition. Document review, interviews with maintenance workers, and visual inspection using the BCA form, which follows JKR 21602-0004-131JKR, were used as a research instruments. The finding shows that the overall rating for the building’s condition is 8, indicating good condition and implying the need for condition-based maintenance on certain components. This study can assist development and maintenance management in better planning and prioritizing maintenance activities to ensure the building is kept in good condition and provides comfort and safety to students and other building occupants.